Enhancing Balance Skills in Secondary School Sports Students through VR Simulation Training: An Experimental Study - Miao, Feng; Yan, Jun (Journal of Theory and Practice of Contemporary Education, 2023)
Virtual reality (VR) simulation training has emerged as a promising approach to enhance balance skills in sports students. VR simulations offer a safe and controlled environment that replicates real-life situations, allowing students to practice and refine their balance skills in an immersive and interactive manner. This experimental study aims to investigate the effectiveness of VR simulation training in improving balance skills among secondary school sports students.